Social worlds and the leisure experience - Stebbins, Robert A., 1938- (Bingley, U.K. : Emerald Publishing Limited, 2018)
Anselm Strauss observed 40 years ago that the idea of social world was suffering from weak conceptualization and application to those areas of social life where this formation figures prominently in everyday activities. This book provides a coherent statement about what social worlds consist of, what they do, where they fit in social theory.
Includes bibliographical references and index.
Print version record
Keywords: Social perception; Social Science -- Sociology -- General; Social, group or collective psychology